2014
DOI: 10.1097/jto.0000000000000072
|View full text |Cite
|
Sign up to set email alerts
|

Parallel FISH and Immunohistochemical Studies of ALK Status in 3244 Non–Small-Cell Lung Cancers Reveal Major Discordances

Abstract: This study highlights the feasibility of systematic NSCLC testing by both FISH and IHC in routine practice. Many preanalytical factors may account for the apparent discrepancies between both methods, suggesting that hierarchical screening may underscore ALK-positive cases. This significant level of discrepancy supports the need of combined testing to optimize the detection of ALK-inhibitor-eligible patients given that some patients with discordant testing were found to respond to crizotinib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 47 publications
(71 reference statements)
7
129
1
5
Order By: Relevance
“…For two of these FISH + /IHC − cases, presence of variant 1 was identified by qRT-PCR. Overall, our discordance rate is far from that reported by CABILLIC et al [20]. This previous study, based on the daily practice of two French molecular genetics platforms, reported a very low rate of positive cases by both FISH and IHC (80 (53%) out of 150), reaching 59% (80 out of 135) if noncontributive cases were excluded.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…For two of these FISH + /IHC − cases, presence of variant 1 was identified by qRT-PCR. Overall, our discordance rate is far from that reported by CABILLIC et al [20]. This previous study, based on the daily practice of two French molecular genetics platforms, reported a very low rate of positive cases by both FISH and IHC (80 (53%) out of 150), reaching 59% (80 out of 135) if noncontributive cases were excluded.…”
Section: Discussioncontrasting
confidence: 52%
“…The present study is the second largest study to date on ALK rearrangements in adenocarcinoma in French Caucasian patients [20]. However, our study does not reflect ALK rearrangement epidemiology or FISH: fluorescence in situ hybridisation; NI: not interpretable; ALK: anaplastic lymphoma kinase; IHC: immunohistochemistry; V: variant; WT: wild type; Abs: antibodies; NA: not available.…”
Section: Discussionmentioning
confidence: 71%
“…163e165 Importantly, however, clinical outcomes of patients with discrepant FISH and IHC results have not shown a consistent pattern of superiority of one method over the other. 156,166 Although at the time of writing RT-PCR and NGS are not approved by FDA in the United States as first-line methods for determining ALK status in selection of patients for ALK inhibitor therapy, these approaches have shown comparable performance with IHC 163e165 when designed to detect the majority of fusions, and are standard practice in many other countries. 163e165,167 These methods are highly specific for most fusions, 97,168,169 and patients with positive results should be treated with an ALK inhibitor, although patients with negative results may benefit from a more sensitive method to exclude the possibility of a variant fusion.…”
Section: Recommendationmentioning
confidence: 99%
“…Of 3244 cases, 150 were found to be ALK positive by FISH and/or positive by IHC, but only 80 of those samples were found to be positive by both FISH and IHC. They concluded that one-quarter of ALK -positive samples would have been missed had only single FISH or IHC testing been employed [14]. Both these tests are approved for the diagnosis of ALK -positive patients and most institutions use one of the two tests.…”
Section: Testing For Anaplastic Lymphoma Kinase (Alk)mentioning
confidence: 99%